Sea spray aerosol chemical composition: elemental and molecular mimics for laboratory studies of heterogeneous and multiphase reactions. (16th February 2018) - Bertram, Timothy H.; Cochran, Richard E.; Grassian, Vicki H.; Stone, Elizabeth A.
Abstract : Schematic representation of the reactive uptake of N2 O5 to a sea spray aerosol particle containing a thick organic film. Abstract : Sea spray aerosol particles (SSA), formed through wave breaking at the ocean surface, contribute to natural aerosol particle concentrations in remote regions of Earth's atmosphere, and alter the direct and indirect effects of aerosol particles on Earth's radiation budget. In addition, sea spray aerosol serves as suspended surface area that can catalyze trace gas reactions. It has been shown repeatedly that sea spray aerosol is heavily enriched in organic material compared to the surface ocean. The selective enrichment of organic material complicates the selection of representative molecular mimics of SSA for laboratory or computational studies. In this review, we first provide a short introduction to SSA formation processes and discuss chemical transformations of SSA that occur in polluted coastal regions and remote pristine air. We then focus on existing literature of the chemical composition of nascent SSA generated in controlled laboratory experiments and field investigations. We combine the evidence on the chemical properties of nascent SSA with literature measurements of SSA water uptake to assess SSA molecular composition and liquid water content. Efforts to speciate SSA organic material into molecular classes and specific molecules have led to the identification of saccharides, alkanes, free fatty acids, anionic surfactants, dicarboxylic acids, amino acids, proteinaceous matter, and other large macromolecules. However to date, less than 25% of the organic mass of nascent SSA has been quantified at a molecular level. As discussed here, quantitative measurements of size resolved elemental ratios, combined with determinations of water uptake properties, provides unique insight on the concentration of ions within SSA as a function of particle size, pointing to a controlling role for relative humidity and the hygroscopicity of SSA organic material at small particle diameters.